Characterization of clinical, laboratory, IL-6 serum levels, and IL-6-174 G/C genetic polymorphisms in patients with rheumatoid arthritis and Sjögren’s syndrome - Melo,Thayanara Silva (2021)
SUMMARY OBJECTIVE: This study aimed to characterize the clinical (disease activity and exocrine gland function), laboratory, interleukin 6 (IL-6) serum levels, and IL-6-174G/C (rs1800795) genetic polymorphisms among rheumatoid arthritis (RA), RA plus Sjögren’s syndrome (RA+SS), and control subjects. METHODS: A case-control study enrolling 137 women (52±11 years old) were divided into three groups as follows: RA (n=70), RA+SS (n=29), and healthy control (C, n=38). Individuals underwent clinical evaluation composed of Schirmer’s test, unstimulated salivary flow rate, and evaluation of disease activity and functional capacity (Disease Activity Score [DAS28] and Health Assessment Questionnaire [HAQ]). IL-6 serum levels and IL-6-174G/C polymorphisms were assessed. RESULTS: RA and RA+SS presented higher serum levels of IL-6 than controls (p<0.001). Also, higher IL-6 levels were related to swollen joints (p=0.038), limited functional capacity (p=0.004), and disease activity (p≤0.001). However, neither IL-6-174G/C genetic polymorphism nor its allele frequency was associated with RA or RA+SS. CONCLUSION: IL-6 serum is an important marker of RA activity and functional incapacity, but IL-6-174G/C genetic polymorphism did not differ among healthy controls and cases.